Oil Exporters' Economic Development in an Interdependent World - Amuzegar, Jahangir (Occasional Papers; Occasional Paper, 1983)
Not unpredictably, there is a complex energy bind as we approach the end of the twentieth century. The oil importing industrial countries have anchored their industries, their means of transportation, their home comfort- in short, their whole energy-dependent lifestyle-largely to hydrocarbon fuels.